(Second) Harmonic Disharmony: Nonlinear Microscopy Shines New Light on the Pathology of Atherosclerosis. (22nd June 2016) - Watson, Shana R.; Lessner, Susan M.
Abstract: There has been increasing interest in second harmonic generation (SHG) imaging approaches for the investigation of atherosclerosis due to the deep penetration and three-dimensional sectioning capabilities of the nonlinear optical microscope. Atherosclerosis involves remodeling or alteration of the collagenous framework in affected vessels. The disease is often characterized by excessive collagen deposition and altered collagen organization. SHG has the capability to accurately characterize collagen structure, which is an essential component in understanding atherosclerotic lesion development and progression. As a structure-based imaging modality, SHG is most impactful in atherosclerosis evaluation in conjunction with other, chemically specific nonlinear optics (NLO) techniques to identify additional components of the lesion. These include the use of coherent anti-Stokes Raman scattering and two-photon excitation fluorescence for studying atherosclerosis burden, and application of stimulated Raman scattering to image cholesterol crystals. However, very few NLO studies have attempted to quantitate differences in control versus atherosclerotic states or to correlate the application to clinical situations. This review highlights the potential of SHG imaging to directly and indirectly describe atherosclerosis as a pathological condition.